Avaliação da influência do acabamento superficial na resistência à corrosão do aço SAE 1020 em biodiesel e suas misturas com óleo diesel - Roque, Bruno Alexandre (Universidade Federal de São Carlos, 2021)
This work evaluated the influence of surface finish resulting from milling on the corrosion resistance of SAE 1020 steel parts in biodiesel (B100) and its blends with petroleum diesel (B15 and B30), through tests of total immersion, crevice corrosion and vapor phase for 2400h at room temperature. For milling, three tool displacement configurations were used, and three parts regions had their surfaces characterized by skewness (Ssk), kurtosis (Sku) and reduced valley depth (Svk) parameters. The statistical analysis of these parameters showed that the three machining configurations produced surfaces with differences related to the predominance of peaks and valleys, with the peaks of the first configuration being steeper than those of the first configuration, suggesting that the tool displacement strategy could present a correlation with the susceptibility to corrosion of the parts. After the tests, it was found that the blends B15, B30, biodiesel (B100) and the total immersion, crevice corrosion and vapor phase tests did not produce significant variations in the roughness parameters. However, taking into account only the machining configuration factor, after 2400h the samples of the first configuration showed significant differences in the mean values of Ssk and Sku, indicating that their surfaces had a greater number of valleys than at 0h and suggesting that the peaks of this configuration were responsible for a larger area of exposure to biodiesel and its blends. Although the surfaces of the other configurations presented some changes resulting from the corrosive action of the diesel/biodiesel blends and biodiesel, for these, no significant changes in the roughness parameters were observed. The formation of passive film on the surfaces and the high electrical resistivity of the studied blends (B15 and B30) and biodiesel (B100) may have influenced the results obtained in the immersion tests, thus suggesting the need for a longer time for these regions the parts had more expressive effects resulting from corrosion.
Influence of surface finish on corrosion resistance of SAE 1020 steel in biodiesel and its blends with petroleum diesel
Keywords: Acabamento superficial; Fresamento; Corrosão; Biocombustível; Biodiesel; Surface finish; Milling; Corrosion; Biofuel; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO